Application of Unified Power Flow Controller to Improve the Performance of Wind Energy Conversion System - Alharbi, Yasser Mohammed R. (Curtin University, 2016)
This research introduces the unified power flow controller (UPFC) as a means to improve the overall performance of wind energy conversion system (WECS) through the development of an appropriate control algorithm. Also, application of the proposed UPFC control algorithm has been extended in this research to overcome some problems associated with the internal faults associated with WECS- voltage source converter (VSC), such as miss-fire, fire-through and dc-link faults.